Comparison of Two Retention Appliances with Respect to Clinical Effectiveness in preventing Relapse - Kalia, Ajit; Reddy, C. Munish; Raghav, Pradeep; Khan, AzmatAzha; Kale, Kinjal; Chauhan, Ashish (Journal of Neonatal Surgery, 2025)
OBJECTIVE: This study aimed to compare the clinical effectiveness of Essix and Hawley retainers during the orthodontic retention phase. Methods: Thirty subjects who completed fixed orthodontic treatment were evaluated using the American Board of Orthodontics Phase III Objective Grading System. After appliance removal, participants were randomly assigned to either upper-lower Essix or upper-lower Hawley retainer protocols. All subjects wore their retainers full-time for 6 months (except during meals), then nights-only for another 6 months. Clinical effectiveness was assessed by measuring overjet, overbite, maxillary and mandibular intercanine widths, intermolar widths, arch lengths, irregularity indexes, and lateral cephalometric parameters at three time points: pre-treatment, post-treatment, and post-retention. All measurements were performed by the same investigator. Results: No statistically significant differences were found between the Essix and Hawley groups in overjet, overbite, intercanine widths, intermolar widths, arch lengths, or lateral cephalometric measurements across all time points. Both groups showed a slight, non-significant increase in maxillary and mandibular irregularity indexes from post-treatment to post-retention.